Nuclear matrix and hnRNP share a common structural constituent associated with premessenger RNA. - Gallinaro, H (1983)
Nuclear matrix and heterogeneous nuclear ribonucleoprotein (hnRNP) were compared to establish whether premessenger RNA (premRNA) was associated with a same constituent in both structures. The isolation of nuclear matrix included the removal of chromatin and of 0.4 M KCl-soluble material. HnRNP, isolated by a standard method was also treated by 0.4 M KCl. Both isolation procedures caused the removal of DNA, histones, a fraction of small nuclear RNA and of nonhistone proteins including the hnRNP proteins in the 30 000-40 000 mol. wt. range. High resolution autoradiography showed that hnRNA remained associated with the residual fibrils in both structures. They both contained the same premRNA and maturation products as shown by the analysis of the transcripts of the early region 3 of adenovirus 2. In addition, the small nuclear RNA and protein of the salt-resistant complexes were also present in the matrix. The results are compatible with the idea that the salt-resistant complexes from hnRNP constitute the fibrils associated with premRNA in the nucleoplasmic matrix. The fibrils may be the basic unit of splicing and their organization in matrix might provide the spatial configuration necessary for regulation.